THE ROLE OF SOCIAL MEDIA IN PROMOTING PLASTIC SURGERY - RUSTAMOVA GULSANAM SANJAR QIZI; ISHKOBILOVA KHULKAR (TADQIQOTLAR, 2026)
Annotation (Abstract) English: This article examines the growing influence of  social media on the popularity and acceptance of plastic surgery. It explores how platforms shape beauty standards,  affect  individual  self-perception,  and  encourage  cosmetic  procedures through influencers, advertising, and visual content.